Development of Chemistry Learning Media based on Joyful Learning with Snakes and Ladders Game on Stoichiometry material to Improve Student Learning Outcomes - Janah, Miftakhul; Mitarlis, Mitarlis (Universitas Pendidikan Mandalika, 2024)
This research aims to obtain chemistry learning media based on joyful learning with the snakes and ladders game on stoichiometric material that is suitable for use to improve student learning outcomes based on the validity, practicality and effectiveness of the game. The research method used is the research development (R&D) method with the 4D model by Tigharajan which consists of 4 main stages, define, design, develop and disseminate. However, the development of Joyful Learing-based Chemistry Learning Media with the Snakes and Ladders game has only reached the development stage. The research was carried out at Surabaya State University and SMA Negeri 1 Menganti Gresik. Test the game media using the One Group Pretest-Posttest Design system. Validity is obtained from the assessment of the stoichiometric snake and ladder game media by the validator. Practicality is obtained from the results of observing student activities, observing the implementation of learning activities, and student response questionnaires. Effectiveness is obtained from student learning outcomes. The results of the research show that chemistry learning media based on joyful learning with the snakes and ladders game on stoichiometric material is suitable for improving student learning outcomes with a feasibility score of ≥ 4 in the feasible to very feasible category. The practicality of chemistry learning media based on joyful learning with the snakes and ladders game on stoichiometric material to improve student learning outcomes is said to be suitable for use in terms of the results of observations of student activities which obtained a percentage of 96.81%, the results of observations of learning implementation obtained a percentage of 93.98%, and Student responses obtained a percentage of 91.52%. Then, the effectiveness of chemistry learning media based on joyful learning with the snakes and ladders game on stoichiometry material to improve student learning outcomes which was developed in terms of pretest and posttest scores was declared effective. This is shown by the N-gain score of all students being in the medium to high category and meeting the KKM value, with an average N-gain value of 0.79 with high criteria. This shows that the stoichiometric snakes and ladders game is declared suitable for use as a chemistry learning medium based on joyful learning on stoichiometric material to improve student learning outcomes.